Suppressive effects of the NADPH oxidase inhibitor apocynin on intestinal tumorigenesis in obese KK‐Ay and Apc mutant Min mice. Issue 11 (16th October 2015) - Komiya, Masami; Fujii, Gen; Miyamoto, Shingo; Takahashi, Mami; Ishigamori, Rikako; Onuma, Wakana; Ishino, Kousuke; Totsuka, Yukari; Fujimoto, Kyoko; Mutoh, Michihiro
Abstract : Obesity is a risk factor for colorectal cancer. The accumulation of abdominal fat tissue causes abundant reactive oxygen species production through the activation of NADPH oxidase due to excessive insulin stimulation. The enzyme NADPH oxidase catalyzes the production of reactive oxygen species and evokes the initiation and progression of tumorigenesis. Apocynin is an NADPH oxidase inhibitor that blocks the formation of the NADPH oxidase complex (active form). In this study, we investigated the effects of apocynin on the development of azoxymethane‐induced colonic aberrant crypt foci in obese KK‐ A y mice and on the development of intestinal polyps in Apc mutant Min mice. Six‐week‐old KK‐ A y mice were injected with azoxymethane (200 μg/mouse once per week for 3 weeks) and given 250 mg/L apocynin or 500 mg/L apocynin in their drinking water for 7 weeks. Six‐week‐old Min mice were also treated with 500 mg/L apocynin for 6 weeks. Treatment with apocynin reduced the number of colorectal aberrant crypt foci in KK‐ A y mice by 21% and the number of intestinal polyps in Min mice by 40% compared with untreated mice. Both groups of mice tended to show improved oxidation of serum low‐density lipoprotein and 8‐oxo‐2′‐deoxyguanosine adducts in their adipose tissues. In addition, the inducible nitric oxide synthase mRNA levels in polyp tissues decreased. Moreover, apocynin was shown to suppress nuclear factor‐κB transcriptional activity in vitro . These results suggest that apocynin and other NADPH oxidase inhibitors may be effective colorectal cancer chemopreventive agents. Abstract : We demonstrated the suppressive effect of NADPH oxidase inhibitor, apocynin on the number of azoxymethane (AOM)‐induced colorectal aberrant crypt foci (ACF) in obese KK‐Ay mice and intestinal polyp development in Min mice. The mechanism involved in the suppressive effect of apocynin treatment on intestinal polyp formation in Min mice was partly explained by suppression of inducible nitric oxide synthase (iNOS). Moreover, apocynin is demonstrated to suppress NF‐κB transcriptional activity in an in vitro setting.